2022
DOI: 10.1111/gcb.16282
|View full text |Cite
|
Sign up to set email alerts
|

Opposing global change drivers counterbalance trends in breeding North American monarch butterflies

Abstract: Many insects are in clear decline, with monarch butterflies (Danaus plexippus) drawing particular attention as a flagship species. It is well documented that, among migratory populations, numbers of overwintering monarchs have been falling across several decades, but trends among breeding monarchs are less clear. Here, we compile >135,000 monarch observations between 1993 and 2018 from the North American Butterfly Association's annual butterfly count to examine spatiotemporal patterns and potential drivers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
(112 reference statements)
0
11
3
Order By: Relevance
“…It is not uncommon for positive density dependence in one life cycle stage to be counterbalanced by demographic or behavioral changes at other life cycle stages (Levitan 1991, Shuai et al 2020, Stephens et al 1999). Some past studies of eastern monarch butterflies have suggested an opposite pattern of demographic compensation to our results for western monarchs: faster declines in winter than summer in the east (Inamine et al 2016, Crossley et al 2022), and faster recovery of winter population counts than breeding range size in our data. The difference in findings may arise in part because the summer counts used in Inamine et al (2016) and Crossley et al (2022) represent only a portion of the eastern monarch breeding range, and are likely biased toward higher-quality habitat (Pleasants et al 2017).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…It is not uncommon for positive density dependence in one life cycle stage to be counterbalanced by demographic or behavioral changes at other life cycle stages (Levitan 1991, Shuai et al 2020, Stephens et al 1999). Some past studies of eastern monarch butterflies have suggested an opposite pattern of demographic compensation to our results for western monarchs: faster declines in winter than summer in the east (Inamine et al 2016, Crossley et al 2022), and faster recovery of winter population counts than breeding range size in our data. The difference in findings may arise in part because the summer counts used in Inamine et al (2016) and Crossley et al (2022) represent only a portion of the eastern monarch breeding range, and are likely biased toward higher-quality habitat (Pleasants et al 2017).…”
Section: Discussioncontrasting
confidence: 68%
“…It is not uncommon for positive density dependence in one life cycle stage to be counterbalanced by demographic or behavioral changes at other life cycle stages (Levitan 1991, Shuai et al 2020, Stephens et al 1999. Some past studies of eastern monarch butterflies have suggested an opposite pattern of demographic compensation to our results for western monarchs: faster declines in winter than summer in the east (Inamine et al 2016, Crossley et al 2022, and faster recovery of winter population counts than breeding range size in our data.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…We still know relatively little about how climate change affects the abundance of insects in different populations across entire continents (but see; Crossley et al, 2021Crossley et al, , 2022Outhwaite et al, 2022;Soroye et al, 2020;Warren et al, 2018). To date, most large-scale insect surveys have been designed primarily to examine diversity rather than biomass or abundance (e.g., Steinke et al, 2017), or have focused on specific taxa, such as bumblebees (Kerr et al, 2015;Soroye et al, 2020;Weaver & Mallinger, 2022) or butterflies (e.g., Crone et al, 2019;Forister et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Macgregor et al 2019;Thomas et al 2019). Indeed, a recent large study of trends in breeding North American monarch butterflies found no evidence for a ubiquitous decline (Crossley et al 2022).…”
Section: Introductionmentioning
confidence: 99%